IMPROVING STUDENTS’ SELF EFFICACY IN SPEAKING ENGLISH BY USING GROUP-PRESENTATION - Atayeva M.; Basikin, M.; Kassymova G. K.; Sydyk L; Triyono M. B.; Arpentieva M. R.; Dossayeva S. K.; Kivlenok T. V.; Klepach Yulia Vladimirovna (Scientific Journal of Pedagogy and Economics, 2019)
High level of self-efficacy is linked with good performance in language learning tasks in the various language domains and is considered an individual’s belief about personal abilities achieved through practical performance. Consequently, this action research project aimed atidentifyingif the group presentation in English can improve students’ self-efficacy in speaking English in the classroom. In this study, 20 female students of grade XI Madrasah Aliyah PSM Banaran had been chosen. The research was held in two cycles, and each cycle was divided into three meetings. 45 minutes were spent for each meeting. The data of this study were obtained through “English Self-Efficacy Scale” and in order to identify the learners’ needs, interview questions were designed. After comparing the data of the English self-efficacy questionnaire, the findings showed that if the students worked frequently together with friends, even less active students could develop their self-efficacy and performed well in English without any anxiety. The group - presentation had great influence not only on students’ self- efficacy, but also on their English language speaking fluency.